519 Outcomes of Management with Ilizarov Frames in Bone Infection: An Observational Study. (12th October 2021) - Marshall, C; Butler, J
Abstract: Aim: The successful treatment and eradication of bone infection requires a multifaceted approach and may recur even after excision if resultant bone void is not managed effectively. This paper aims to review the clinical effectiveness of antibiotic-impregnated bone void filler and current empirical antibiotic guidelines. Method: We report a retrospective study of 18 patients with chronic osteomyelitis following injury or surgery managed via Ilizarov Ring Fixator (IRF). All patients were managed by IRF stabilisation procedures with debridement, microbiological sampling, and bone void filling with antibiotic-impregnated biocomposite material, in addition to culture-specific systemic antimicrobial therapy. Results: Patients were followed up for a mean of 15.9 months. Infection was eradicated in 94.1% of patients in a grossly comorbid demographic. Comorbidities associated with increased risk of osteomyelitis were noted in 72.2% of patients. Anaerobic bacteria were identified in culture for four (22.2%) of the 18 patients. Conclusions: We detected a higher than suspected growth of anaerobes in our samples, suggesting the need for metronidazole in empirical antibiotic treatment. This study would suggest that the use of STIMULAN® may be preferable in this National Health Service from a cost-effect perspective, as our results are comparable to those using other bone void fillers.